Analisa Jarak Center Lubang Connecting Rod diluar Standar pada PT. XYZ - Ananda Agung Prasetiyo; Deri Teguh Santoso (Jurnal Serambi Engineering, 2024)
PT. XYZ as a manufacturer of commercial vehicles and diesel engines has an important role in the automotive industry. This company consists of several departments, one of which is machining and assembly. Dynamic industrial developments encourage companies to continue to innovate in order to remain relevant, competitive, and develop. Increasing competition in the business world will mean that consumers have more choices in choosing products. Therefore, to have competitiveness and survive competition with other products. This research seems to focus on identifying types of defects, their causes, and providing alternative recommendations for improvement to increase product competitiveness at the PT. Based on identifying factors that cause product defects through a fishbone diagram, namely human, machine and method factors. The proposal given in this research is to make parts or make tools such as Shim Plates which are used to help an object to be stable (connecting rod).